Everyday life on the American frontier - Wright, Louis B. (Louis Booker), 1899-1984. (New York, Wright, 1968)
Discusses the unique and difficult life in America's frontier towns as the frontier expanded westward from colonial Virginia to California and back to Nebraska.
Bibliography: p. 248-252.
Keywords: Frontier and pioneer life -- United States -- Juvenile literature; Frontier and pioneer life